(untitled) (International Journal of Social Science, Commerce & Management Studies, 2026)
Within the span of less than ten years, India has catapulted itself to become one of the world’s fastest-growing digital payment markets and is moving towards a near-cashless retail environment. This paper is based only on secondary data published by the Reserve Bank of India (RBI), the National Payments Corporation of India (NPCI) and allied industry sources and compares the adoption and growth of different digital payment instruments in India from 2018 to 2025. The RBI Digital Payments Index (RBI-DPI) is used as a composite indicator and instrument-level data in volumes and values for Unified Payments Interface (UPI), credit card, debit card, and NEFT-IMPS is used to trend the indicators and calculate growth rates. The results reveal a more than fourfold growth of RBI-DPI from 100 to 493.22 from March 2018 to March 2025. The biggest growth driver is UPI, which was around 1,207 million transactions in FY2018 and is expected to touch 185 billion transactions in 2025 and make up almost 85 percent of digital payment volume by the first half of 2025. The study also shows how there is a structural shift taking place in card payments as credit card transactions grew more than double whereas debit card transactions have seen a drastic decline due to UPI taking over low value retail transactions. The paper finds that the digital payment growth in India is one of instrument substitution and not of uniform growth, and that policy, zero merchant-discount-rate economics, and ubiquity of QR code infrastructure are the key enablers. Limitations relating to secondary-data comparability and avenues for future primary research are discussed.